The Effect of Project Based Learning (PjBL) Learning Model on Students' Science Process Skills on Colloidal Topic - Nurbani Jusuf; Anugrah Ricky Wijaya; I Wayan Dasna (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: This research focuses on applying the project-based learning model in teaching chemistry by using local wisdom in the ternate area. This study is to examine differences in science process skills of students who are taught with project-based learning models and students who are taught with conventional models on colloidal material in terms of achievement motivation, using quasi-experimental design designs (posttest only group). The sample in this study was conducted in one of the MAN in Ternate City. The results of the study show that there are significant differences in science process skills and student achievement motivation using project-based learning in the experimental class and conventional learning in the control class.Abstrak: Penelitian ini berfokus pada penerapan model pembelajaran berbasis proyek dalam pengajaran kimia dengan menggunakan kearifan lokal di daerah ternate dan menguji perbedaan keterampilan proses sains siswa yang dibelajarkan dengan model pembelajaran project based learning dan siswa yang dibelajarkan dengan model konvensional pada materi koloid yang ditinjau dari motivasi berprestasi, dengan menggunakan desain rancangan eksperimental semu (posttest only grup). Sampel dalam penelitian ini dilakukan di salah satu MAN di Kota Ternate. Hasil penelitian menunjukkan bahwa ada perbedaan yang signifikan pada keterampilan proses sains dan motivasi berprestasi siswa menggunakan pembelajaran berbasis proyek untuk kelas eksprimen dan pembelajaran konvensional di kelas kontrol